2023
DOI: 10.1364/optica.480292
|View full text |Cite
|
Sign up to set email alerts
|

Large circular dichroism in the emission from an incandescent metasurface

Abstract: Compact sources in the mid-wave infrared (MWIR) are needed for applications ranging from spectroscopy to free-space communication. Ultrathin incandescent metasurfaces are promising candidates, offering the possibility to tune the emission spectrum, directivity, and modulation speed. However, control over polarization remains a challenge, especially when it comes to the emission of circularly polarized light. Here, we report the emission of polarized MWIR radiation from a 700 nm thick incandescent chiral metasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The same approach could be used to design photoluminescent metasurfaces controlling the emitted polarization as reported recently in the context of thermal emission. 30 The method could also be applied to optimize dielectric photoluminescent metasurfaces, 23,60,61 which could enable sources with narrower emission cones, as well as electroluminescent metasurfaces. 16,17,62…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same approach could be used to design photoluminescent metasurfaces controlling the emitted polarization as reported recently in the context of thermal emission. 30 The method could also be applied to optimize dielectric photoluminescent metasurfaces, 23,60,61 which could enable sources with narrower emission cones, as well as electroluminescent metasurfaces. 16,17,62…”
Section: Discussionmentioning
confidence: 99%
“…Kirchhoff’s law has been initially used to design thermal sources and to optimize simultaneously directionality, polarization, and emitted power by designing emissivities approaching 1. Recent works have shown that the local Kirchhoff’s law can be successfully used to analyze not only thermal emission but also complex photoluminescent emission situations. In this article, we show that the local form of Kirchhoff’s law can be used to optimize the design of a light-emitting metasurface . We extend to photoluminescence what was achieved in the context of thermal emission, with a method of designing directional photoluminescent metasurfaces via the local Kirchhoff’s law.…”
mentioning
confidence: 84%
“…Additional control over the THz thermal emission, e.g. spectral content, directionality and polarization, can be achieved combining our approach with existing techniques based on microantenna arrays, [14][15][16][17][18][19][20][21] making the technique relevant beyond imaging applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some chiral metasurfaces integrated with graphene have been proposed to achieve the tunable CD [15,16]. The chiral metamaterials and metasurfaces operating in the mid-IR wavelength range can also be used as the polarizationdependent thermal absorbers and emitters to control the response of a thermophotovoltaics device and increase the thermal energy conversion efficiency [17]. Metamaterials face significant challenges in practical applications due to complex fabrication processes, scalability issues, and high costs.…”
Section: Introductionmentioning
confidence: 99%